PEMBELAJARAN METODE KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR BAHASA ARAB (QOWA’ID) MAHASISWA PERBANKAN SYARI’AH IAIM NU METRO LAMPUNG TAHUN 2017 - Muhammad Syaifullah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2017)
Learning Arabic qowa'id student Syari'ah Banking Second semester Ma'arif Institute of Islamic NU Metro Lampung still not maximized. Students have difficulties to understand Arabic qowa'id material. Student learning motivation is also low. This is what makes researchers want to do research in that class. Problems to be expressed in this research are: (1) How is the application of Arabic qowa'id learning with cooperative model of jigsaw method in class A, second semester of Syari'ah Banking, (2) How to improve learning qowa'id after getting learning with cooperative learning model of jigsaw method, (3) What are the advantages and disadvantages of implementing cooperative Arabic qawaid in class A with jigsaw method. This research is a classroom action research conducted in two cycles. Each cycle is done in a cycle consisting of four stages: planning, execution, observation and reflection. The results of this study indicate an increase from cycle I of cycle II. The average class cycle I is 60.83 and the average of cycle II is 71. The students also show behavior change in the positive direction. Student activity is increasing. The improvement of test result is also followed by behavioral and motivational change based on research which has been done by the researcher that through cooperative learning with jigsaw method, Arabic qowa'id learning becomes more fun and easier for students in learning qowa'id. Suggestions that can be given is a lecturer of Arabic language should be more creative in using techniques and learning methods that involve the active role of student learning so that the learning process to get the maximum value. One alternative of learning Arabic qowa'id is by using cooperative learning jigsaw model.